(untitled) - Asian Development Bank (Hà Nội, 2007)
Part one Concepts:definition, Value Chain concepts, A Pro-Poor Entry Point into Value Chain Analysis. Part two Value - chain tools: prioritising value chains for analysis, mapping the value chain, costs and margins, analysing technology, knowledge and upgrading, analysing income in the value chain, analysing employment in the value chain, governance and services, linkages.
Keywords: Poverty,Tình trạng nghèo nàn,Poor,Nghèo đói; Services for,Dịch vụ,Employment,Việc làm